(untitled) (International Seven Journal of Multidisciplinary, 2023)
This study on the entrepreneurship of a family business in the Architecture and Construction segment in the city of Manaus aims to provide a contribution to improve the organization and ensure its continuity in the current competitive market. It addresses the concepts, issues, challenges, and methods of analysis and resolution that help reduce family conflicts and effectively plan the growth and succession of the enterprise that can achieve the company’s objective. For this, it is necessary to initially examine the organizational structure of the family business, in order to identify the obstacles faced in the market.